2022
DOI: 10.2186/jpr.jpr_d_22_00108
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution of one-piece and two-piece mini-Implant overdentures with various attachment systems and diameters: A finite element analysis

Abstract: Implant overdentures have become a reliable treatment option for edentulous patients because of their enhanced retention, stability, masticatory performance, and higher patient satisfaction compared to conventional complete dentures [1,2]. Mini-implants have a reduced diameter of <3.0 mm and are manufactured using biocompatible materials used for manufacturing standard-sized implants [3]. Mini-implant overdentures are beneficial alternatives for elderly patients with severely resorbed mandibles or physical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In addition, the monolithic structure of one-piece mini-implants also avoids the risk of bacterial microleakage at the abutment-implant interface, which improves the maintenance of bone levels around implants in the long term (do Nascimento et al, 2012). It was also reported that onepiece mini implants show lower levels of biomechanical stress compared to two-piece mini-implants (Trang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the monolithic structure of one-piece mini-implants also avoids the risk of bacterial microleakage at the abutment-implant interface, which improves the maintenance of bone levels around implants in the long term (do Nascimento et al, 2012). It was also reported that onepiece mini implants show lower levels of biomechanical stress compared to two-piece mini-implants (Trang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%